Kajian Potensi Sumberdaya Lahan Untuk Pengembangan Tanaman Hortikultura Di Kecamatan Manggis Kabupaten Karangasem - I MADE MEGA; I NYOMAN PUJA; I NYOMAN SUNARTA; I WAYAN NUARSA (Agrotrop : Journal on Agriculture Science, 2014)
The Study of Land Resource Potentials at Manggis District, Karangasem Regency forDevelopment of Horticulture Crops.The objective of the research was to study the potential ofland resources for growing horticulture crops at Manggis District, Karangasem Regency. Soil surveyand laboratory analysis were used in this research. The parameters of soil characteristics observedwere soil morphology in the fields, and physical and chemical properties. The results showed that thelands of Manggis District classified into ‘suitable enough’ until ‘very suitable’ for growing horticulturecrops. The limited factors were root medium; nutrient retention and terrains